1996
DOI: 10.1002/bjs.1800831108
|View full text |Cite
|
Sign up to set email alerts
|

A Western surgical experience of peripheral cholangiocarcinoma

Abstract: The aim of this retrospective study was to analyse outcome in 31 European patients operated on for peripheral cholangiocarcinoma between 1988 and 1995 (hilar cholangiocarcinoma was excluded). Before 1992, in addition to conventional resection, patients with irresectable tumour and with no extrahepatic metastasis underwent total hepatectomy with liver transplantation. Mild abdominal pain was the most frequent presenting clinical sign (11 of 31 patients) and jaundice was present in only four patients. Preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 19 publications
4
45
0
2
Order By: Relevance
“…The English-language literature on PCC has reported only a few long-term survivors, 10,23 and the 5-year survival rate after curative resection has been reported to be approximately 40%. [3][4][5][6][7][8][9]24 Compared with other series of PCC, the IG type had a much better prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The English-language literature on PCC has reported only a few long-term survivors, 10,23 and the 5-year survival rate after curative resection has been reported to be approximately 40%. [3][4][5][6][7][8][9]24 Compared with other series of PCC, the IG type had a much better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because the lesion is advanced by the time of diagnosis, 2 the possibility of surgical resection is limited and the prognosis is generally poor. [3][4][5][6][7][8][9] In 1992, Yamamoto et al 10 classified PCC into 2 types, mass-forming (MF) and periductal-infiltrating (PI), and showed their different clinical behaviors. The MF type creates an apparent lesion in the liver, with frequent remnant hepatic recurrence after resection.…”
mentioning
confidence: 99%
“…A partial hepatectomy with removal of the involved bile ducts is performed. Five year patient survival ranges from approximately 20-43%, the higher survival stems from careful patient selection (61)(62)(63)(64). In the remainder, recurrent disease is the norm.…”
Section: Therapy Curative Surgical Resectionmentioning
confidence: 99%
“…The prognosis of patients with IHCC is generally poor due to the advanced stage of the disease at presentation [5,6]. Following diagnosis, the majority of patients with IHCC have a reported median survival of less than 9 months [7,8]. Nevertheless, recent published literature has shown that aggressive surgical resection does improve long-term survival in selected cases [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%